Terahertz rectification in ring-shaped quantum barriers. Issue 1 (December 2018) - Kang, Taehee; Kim, R.; Choi, Geunchang; Lee, Jaiu; Park, Hyunwoo; Jeon, Hyeongtag; Park, Cheol-Hwan; Kim, Dai-Sik
Abstract Tunneling is the most fundamental quantum mechanical phenomenon with wide-ranging applications. Matter waves such as electrons in solids can tunnel through a one-dimensional potential barrier, e.g. an insulating layer sandwiched between conductors. A general approach to control tunneling currents is to apply voltage across the barrier. Here, we form closed loops of tunneling barriers exposed to external optical control to manipulate ultrafast tunneling electrons. Eddy currents induced by incoming electromagnetic pulses project upon the ring, spatiotemporally changing the local potential. The total tunneling current which is determined by the sum of contributions from all the parts along the perimeter is critically dependent upon the symmetry of the loop and the polarization of the incident fields, enabling full-wave rectification of terahertz pulses. By introducing global geometry and local operation to current-driven circuitry, our work provides a novel platform for ultrafast optoelectronics, macroscopic quantum phenomena, energy harvesting, and multi-functional quantum devices. Many experiments have been performed that study rectification by exciting electrons to tunnel across a single quantum barrier. Here, the authors take a 2-dimensional approach by combining 2D closed-loop tunneling barriers with broken symmetry to enable geometrically controllable rectification of THz fields.